A general overview and comparative interpretation on element‐specific X‐ray spectroscopy techniques: XPS, XAS, and XRS. (14th June 2022) - Ketenoglu, Didem
Abstract: X‐ray photoelectron spectroscopy (XPS), X‐ray absorption spectroscopy (XAS) and X‐ray Raman scattering (XRS) spectroscopy are the element‐specific tools providing local electronic and chemical structure insights. XPS is widely used for qualitative/quantitative surface analysis of solids and replaced by synchrotron‐based ambient pressure‐XPS and hard‐XPS to benefit from the advantages of near‐ambient pressures and hard X‐rays to study complex sample environments. XAS is a well‐established soft and hard X‐ray probe to examine the coordination, spin and oxidation states in solids, liquids and gases with high resolutions and short data acquisition time. XRS, using the hard X‐rays of 10 keV, is preferred to conventional XAS and XPS in the study of soft X‐ray absorption edges such as C, O, Li K‐edges bulk‐sensitively in vacuum‐free medium for energy storage systems during working operations, inner Earth elements under realistic conditions, probing chemical and biological reactions in the liquid phase, C speciation in archeological and paleontological samples and direct tomography. In this study, first the basics of XPS, XAS, and XRS techniques with their advantages and limitations are introduced to provide a general overview. In the Results and Discussion, the particular emphasis is given to the comparison of XPS, XAS, and XRS with the interpretation of the spectroscopic signatures for organic carbonate‐based electrolytes. The computed C 1 s binding energy shifts for ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC), and diethyl carbonate (DEC) are presented to discuss the XPS peak assignments and the performed C K‐edge XRS measurements of 1 M LiPF6 in DMC and EC are given for a detailed discussion of the XRS spectra. C 1 s XPS, C K‐edge XAS, and XRS of PC from the literature are discussed to interpret the spectra of each technique comparatively.